Cognitive and Interpersonal Features of Intellectual Humility. (June 2017) - Leary, Mark R.; Diebels, Kate J.; Davisson, Erin K.; Jongman-Sereno, Katrina P.; Isherwood, Jennifer C.; Raimi, Kaitlin T.; Deffler, Samantha A.; Hoyle, Rick H.
Four studies examined intellectual humility—the degree to which people recognize that their beliefs might be wrong. Using a new Intellectual Humility (IH) Scale, Study 1 showed that intellectual humility was associated with variables related to openness, curiosity, tolerance of ambiguity, and low dogmatism. Study 2 revealed that participants high in intellectual humility were less certain that their beliefs about religion were correct and judged people less on the basis of their religious opinions. In Study 3, participants high in intellectual humility were less inclined to think that politicians who changed their attitudes were "flip-flopping, " and Study 4 showed that people high in intellectual humility were more attuned to the strength of persuasive arguments than those who were low. In addition to extending our understanding of intellectual humility, this research demonstrates that the IH Scale is a valid measure of the degree to which people recognize that their beliefs are fallible.